A study on the usability and usefulness of Filipiniana.net digital library - Tingson, Leanne Pearl Dreo; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2011)
The development of digital libraries is steadily increasing and it is the concern of the Library and Information Science community to ensure that the users get quality information from this new advent. In order to do so evaluation of libraries as determined by patrons and end-users must be performed.
A qualitative study was conducted to evaluate the usability and usefulness of the web-based digital library Filipiniana.net, questionnaires were administered to random undergraduate students taking Philippine Studies courses. The study employed the Interaction Triptych Framework in evaluating the digital library which focuses on the interactions between digital library components.
The results revealed that users have positive perceptions on the usability and usefulness of Filipiniana.net digital library and certain individual attributes were found to have significant effects on the overall usability and usefulness of the digital library. The principal conclusion was that users have an inclination to use digital libraries that fit their needs. Recommendations are summarized based on users' feedbacks on their experience in interacting with Filipiniana.net.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Digital libraries -- Philippines -- Use studies